Time Management and Priority Scale as Strategies to Improve Learning Motivation and Self-Leadership at SMP Ma'arif, Batu City - Maulida, Adiska Rahma; Sabrina, Alifah Tesha Nur; Fadilla, Asylia Rahma; Amanda, Dian; Azizah, Elisa Lutfiyah; Maulidya, Nalaina Izzaty; Romadlona, Noham Arum (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
According to the World Health Organization, junior high school students have an age of 10-19 years which is a transition period from childhood to adolescence which has a leadership spirit. The target of this service activity is class 8C students as many as 28 people at SMP Ma'Arif, Batu City. Time management and prioritization play an important role in leadership because it helps to increase effectiveness, efficiency and productivity so as to get the goals achieved. This community service activity aims to increase knowledge about time management and priority scale so as to increase learning motivation and self-leadership of students in class 8C of SMP Ma'Arif, Batu City. The method used is the lecture method through Power Point media. The implementation of the activity began through the preparation stage, pre-test, presentation of leadership materials on time management and prioritization, and post-test. The pre-test results showed a high knowledge category of 39% and a post-test of 68% so that there was an increase of 27% in terms of knowledge. The results of the service show that there is an increase in knowledge about time management and priority scale so that it can increase learning motivation and self-leadership. The conclusion of this service activity is that through socialization by providing leadership material regarding time management and priority scale, it can increase learning motivation and self-leadership of students in class 8C of SMP Ma’Arif, Batu City.